A Discussion on Ways to Integrate Artificial Intelligence with Pinnacles of Technology in the Contemporary World - Joe, S. Naveen (International Journal of Computer Sciences and Engineering, 2025)
Artificial Intelligence is one of the most prominent fields in computer sciences in the twenty first century. Using the combination of machine learning and neural networking various autonomous assistants can be built serving a wide range of purposes. The integration of AI with other fields would mean a ground breaking feat in the field of technology, perhaps comparable to the innovation of mobile phones and their integration with internet. The IoT AI integration is crucial for further development in technology as it improves connectivity greatly between devices. A rover is built using this union of technologies. The rover is equipped with a processor to make calculations and handle the AI component. With the advancements in strong AI the capacity of performance that can be achieved by the Rover becomes limitless. The other integration with a possible future is the one with quantum technologies, with an increased amount of rovers there can be quantum server farms(for speed) set up in geographically suitable regions which would increase the speed and connectivity of the internet and more importantly the security as it is ensured by the use of lava lamp or compound pendulum encryption.